Telehealth Integration into Pharmacy Practice Curricula: An Exploratory Survey of Faculty Perception - Jennifer M. Bingham; David R. Axon (MDPI AG, 2023)
(1) Background: The use of telehealth in the United States during the coronavirus disease 2019 pandemic was accelerated and there was a lack of telehealth training programs available to clinicians of all levels. At the onset of the pandemic, the American Association of Colleges of Pharmacy (AACP) had no educational outcomes or professional activity standards for the inclusion of telehealth in the didactic Doctor of Pharmacy curriculum. Yet, in November 2022, the AACP encouraged colleges of pharmacy to include digital health and telehealth. The purpose of this study was to assess faculty perceptions in preparation for a nation-wide survey regarding telehealth integration into pharmacy practice curricula. (2) Methods: An exploratory questionnaire was developed to describe faculty perceptions and opinions of telehealth integration into the pharmacy practice curriculum at a single college of pharmacy. The questionnaire was emailed to 76 faculty members over six weeks in Summer 2022. Data were summarized descriptively. (3) Results: A total of 18 faculty members completed the survey (24% response rate). The responding faculty were typically very aware (median = 4) of telehealth, its benefits, and barriers, and were very comfortable (median = 4) discussing telehealth communication, benefits of telehealth, and barriers of telehealth. Yet, they were less comfortable discussing telehealth applications (median = 2.5). The faculty had a positive perception of telehealth in general (mean = 8.1 ± 1.5), telehealth services (mean = 8.6 ± 1.6), and the incorporation of telehealth instruction into the pharmacy practice curriculum (mean = 7.7 ± 2.7). Most respondents (67%) could discuss telehealth in their course. Lack of time to teach (50%) was the most reported reason by those who did not have plans to incorporate telehealth instruction into their course. (5) Conclusions: This exploratory survey of faculty at one college of pharmacy indicated positive perceptions and opinions of telehealth integration into the Doctor of Pharmacy curriculum. Further efforts to incorporate telehealth into the curriculum at other pharmacy schools is warranted.